Tutorial You tube: English Learning Media Under the Frame Work of Students’ Need Analysis in EFL class - rina herlina (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2019)
This study reports how Tutorial YouTube (TYT) is used to teach English to support learning activity in EFL class in Galuh university considering that the students still require English knowledge to complete and polish what they learn in the classroom. The language media in TYT is presented in Indonesian language because it is only for Indonesian students. In the making of TYT, students' need analysis (SNA) is required to find out students' weakness in learning English. It's usually all about what language features they need and what constructed videos need to be uploaded. The purpose of the study is to find out the process of how non-native English teacher (NNET) proceeds SNA underpinning the construction of TYT for the sake of enhancing students' English performance.This case study took place in one of private universities in West Java. One English teacher, in particular English lecturer, participated for the interview and class observation. The interview result was crosschecked with the classroom observation under the Triangulation process. The goal of Triangulation is to get deep result and finding of the research. Thus, the result shows that NNET uses SNA-based TYT. She observes what the students need by scanning them all the way through during the learning session. If she thinks that her students need enrichment in one of language features, she will construct a TYT and upload it. This kind of classroom observation might scaffold the teacher in teaching English to EFL students since the time allotment in teaching English in the class can not cope with many aspects of language features. The conclusion is TYT, as the learning media, is developed based on SNA and it is fruitfull to be implemented to fulfill what the students need in learning English.